Autonomous Learning Writing Promoted by the Use of Facebook Group - Khairil Razali (IAIN Salatiga, 2013)
In aglobalized world, internet facilities and social media are becoming increasingly important and take a strategic role in most of human activities. One of them is in the education and learning sector. This qualitative research explored the role of a Facebook group to increase students' autonomy in learning writing. The experiment was conducted with qualitative methodology to 6 students as a sample. The process of data collection is done through the media Facebook group which was developed during the data collection through observation and interviews. The research lasted for 30(thirty) days in which researchers became the administrator and facilitator. From the process of collecting and analyzing the data assumed that Facebook group influenced the autonomy and promote independent of students learning in writing. Keywords: Facebook group ; Students autonomy ; Learning writing